Pengaruh lama istirahat terhadap karakteristik karkas dan kualitas fisik daging sapi Brahman Cross Steer - Mukhlas Agung Hidayat; Kuswati Kuswati; Trinil Susilawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The purposes of this study were determine the carcass characteristics and physical meat quality of Brahman Cross Steer on different rest periods. The experiment was conducted on June 2015 at Slaughter house Cianjur Arta Makmur Ltd. in the Cianjur District, West Java. The total number of cattle used in the study was 30 heads of Brahman Cross Steer treated for 18 hours lairage duration and 30 heads of Brahman Cross Steer treated for 3 hours lairage duration from Pasir Tengah feedloter Ltd (Holding Widodo Makmur Perkasa Ltd). The method used a case study. Data were analyzed using unpaired t test. The results showed that the carcass characteristics including slaughtered weight, hot carcass weight, chilled carcass weight and carcass weight loss percentage were not significantly different, while the dressing percentage for 18 hours lairage duration (54.16±1.62%) and 3 hours lairage duration (55.60±2.00%) was significantly different (P<0.05). Physical meat quality including cooking loss and drip loss was not significantly different, while pH on 18 hours lairage duration and 3 hours lairage duration was significantly different (P<0.05). The pH value of meat derived from cattle which treated for 18 hours lairage duration (5.57±0.09) was higher than that of 3 hours lairage duration (5.42±0.11) although it remained normal for pH (5.4-5.7). It was concluded that 18 and 3 hours lairage duration did not affect slaughtered weight, hot carcass weight, chilled carcass weight, and carcass weight loss, but affected the dressing percentage. In addition, the lairage duration did not affect the cooking loss and drip loss but affected the pH value of the meat. Keywords: drip loss, cooking loss, fattening, pH